Evaluasi Kebijakan Pengelolaan Sampah di Desa Bandar Khalipah - Tarigan, Aprianta; Sianturi, Laura Glene; br Sinaga, Melisa; Siringo-ringo, Putri Intan; Naibaho, Vebri Meliarni Oktavia (Universitas Methodist Indonesia, 2024)
Until now, waste management is still a major problem, almost every region experiences this problem. Along with population growth and community activity levels. The research method used is qualitative research with several interview techniques. From the results of observations that have been carried out directly in the field by researchers and the results of interviews with the Village Head and several residents of Bandar Khalipah village, information can be produced that in Bandar Khalipah Village, Percut Sei Tuan District, Deli Serdang Regency, North Sumatra, even though the village government has tried to implement the policy the public to encourage citizens to care about the environment by managing waste properly and correctly is still not implemented well. The public policy implemented by the village government in providing waste management infrastructure in Bandar Khalipah Village was attempted several years ago but has not been implemented well due to several existing factors. The unavailability of TPA (Final Disposal Site) is one of the triggers for many village communities continuing to throw rubbish carelessly, such as in rivers, roadsides near ditches and on empty, uninhabited land.